Innovation in STEM-Based Learning Projects by Utilizing Ocean Wave Theory as a Source of Electrical Energy Using a Four-Pendulum Pontoon - Bayuputri, Daniya Nabila; Safinah, Intan; Gumilang, Putri Citra Ratna; Valiska, Nadita Vera; Mufida, Rosyidatul; Lestari, Nurita Apridiana; Hudha, Muhammad Nur (Studies in Physics Teaching and Learning, 2025)
This study aims to examine the potential of using ocean wave energy as a source of electrical energy through a pontoon system with four pendulums as an innovation in STEM-based learning projects. The method used is a literature review with a descriptive-analytical approach, namely examining various relevant scientific publications related to the design, working principles, and energy conversion efficiency of ocean wave power generation technology. The stages of this research consist of identifying the research topic, conducting a review of scientific sources, examining the design and operational principles of the system, analyzing the collected information, and formulating conclusions along with recommendations. The results of the study show that a pontoon with four pendulums equipped with a Double Free Wheel Rotation Transmission System and a flywheel is able to convert ocean wave motion into electrical energy through a mechanism of converting mechanical energy into electrical energy using a slow-rotating three-phase generator. This system utilizes the swing of the pendulum due to the movement of the pontoon by ocean waves, which is then converted into a rotational motion with high torque to drive the generator. Literature analysis also shows that the stability of the pontoon, the configuration of the pendulums, and the transmission design significantly affect the efficiency of electrical output. Although it has great potential for application in coastal areas and remote islands, further research is needed to optimize the design, improve energy conversion efficiency, and assess its technical and economic feasibility. The findings of this study have implications for strengthening renewable energy literacy within STEM-based learning, while also contributing to raising students’ awareness of environmentally friendly energy utilization. The innovation of the four-pendulum pontoon has the potential to serve as a contextual learning medium that supports the mastery of physics concepts and the development of 21st-century skills. The recommendation of this research is the development of a laboratory- or field-scale prototype and its integration into the science curriculum, enabling students to connect theoretical knowledge with real-world applications of renewable energy.